Avaliação do emprego da radiação micro-ondas para a pirólise de casca de arroz e obtenção de produtos com maior valor agregado - Santos, Mariangela Bruch dos (2024)
In the present study a microwave-assisted pyrolysis system was used for the production of bio-oil, biochar, and biogas using rice husk as raw material. A domestic microwave oven was employed, whose cavity was adapted allowing a quartz reactor passing through it. Argon gas was purged into the system during the process. An aluminum coil immersed in an ice bath was used to condense the oil. The oil was collected in a flask while the gaseous products passed through a gas scrubber before to be released into the atmosphere. The biochar remaining in the reactor after the pyrolysis process was collected. Silicon carbide accessories stacked in the microwave cavity were used to absorb microwave energy and heat the pyrolysis reactor. The pyrolysis time (10, 15, and 20 min) and temperature (500, 600, and 700 °C) were evaluated. The best yields were obtained at 500 °C and 10 minutes of pyrolysis, with values of 58.4 ± 1.0%, 40.2 ± 4.1%, and 3.7 ± 2.8% of bio-oil, biochar, and biogas, respectively. The bio-oil and biochar were then characterized. The bio-oil was analyzed for water content, acidity, metals, and structural information using infrared spectroscopy. For the biochar, moisture content, metals, and structural information were evaluated. Furthermore, the best performance for the microwave-assisted pyrolysis (500 °C, 10 min of pyrolysis) was applied in a fixed-bed pyrolyzer with conventional heating to compare the yields. This resulted in 28.9 ± 3.0%, 33.0 ± 10.0%, and 38.0 ± 7.4% of bio-oil, biochar, and biogas respectively, showing that the proposed microwave-assisted domestic system is more efficient for the production of bio-oil and biochar than the conventional heating system.